PERILAKU OPORTUNISTIK PEJABAT EKSEKUTIF DALAM PENYUSUNAN APBD - Ikhsan Budi Riharjo; Isnadi Isnadi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
Budgeting bring important issues that affect the behavior that had an impact on the effectiveness of government organizations. Government financial management that are not in accordance with the rules is the opportunistic behavior of executive officers so that the push to make mistakes in determining budget allocations in the preparation of Anggaran Pendapatan dan Belanja Daerah (APBD). Purpose of this research is focused on opportunistic behavior of executives who push the influence of direct personnel expenditure, goods and services expenditure and capital expenditure against budget slack prosperity for the people that come from natural resource revenue in accordance with article 33 Undang-Undang Dasar Negara Republik Indonesia tahun 1945. This research is quantitative research using multiple linear regression analysis as well as moderating variables to obtain empirical evidence of research, the data used in the form of secondary data of Region Expense and Revenue Budget all  government  region in Indonesia in 2009, whereas samples in accordance with the requirements of the sampling method amounted to 31 government provence/regency/municipal. Results showed that the opportunistic behavior of the executive officials encourage an increase in personnel expenditure budget directly, goods-services-capital expenditure, which resulted in budget slack for the prosperity of the people that come from natural resource revenues.